Ecological Efficiency of Grass-Based Livestock Husbandry Under the Background of Rural Revitalization: An Empirical Study of Agro-Pastoral Ecotone - He, Dawei; Deng, Xiangzheng; Jin, Gui; Wang, Xinsheng; Zhang, Yali; Sun, Zhigang; Shi, Wenjiao; Zhao, Zhe (Frontiers in Environmental Science, 2022)
As the starting point of addressing “agriculture, rural areas and farmers” issue in the new era, the rural revitalization strategy is inevitable and suits the realistic demand of high-quality development. At present, agro-pastoral ecotone in China is facing a series of ecological degradation and environmental pollution problems. The measurement and analysis of ecological efficiency play an important role in promoting sustainable development of agro-pastoral ecotone. Based on the theoretical discussion and empirical calculation, this study took Tongliao as a case area to explore the ecological efficiency issue. Firstly, ecological efficiency of grass-based livestock husbandry in Tongliao from 2000 to 2019 was calculated by DEA method, then the dynamic change of efficiency was dissected by Malmquist index, and finally multiple factors affecting ecological efficiency of grass-based livestock husbandry were evaluated by Tobit model. The results showed that the ecological efficiency of grass-based livestock husbandry in the counties of Tongliao showed a growing trend from 2000 to 2019, and the average ecological efficiency increased from 0.88 to 1.17; The total factor ecological efficiency of the counties in Tongliao had increased year by year from 2000 to 2019, and it mainly depended on the technological progress; The implementation of the national ecological protection policy and the increase of the output value and employed persons of grass-based livestock husbandry have significantly improved the ecological efficiency. However, the increase in the number of livestock, especially in the case of exceeding the carrying capacity of grassland, was not conducive to the protection of grassland ecology. The key to realize the revitalization of grass-based livestock husbandry in the future is to promote the coordinated development of economy and ecology through the improvement of management level and large-scale and standardized livestock breeding.